MANAGEMENT OF EDUCATION BOARDING SCHOOLS - Gamal Abdul Nasir Zakaria; Desfa Yusmaliana (Edusoshum : Journal of Islamic Education and Social Humanities, 2023)
Management is an important factor in managing an institution, one of which is educational institutions, namely Islamic boarding schools. Islamic boarding school education management has characteristics that are in accordance with Islamic religious teachings and aims to instill Islamic religious values. Islamic boarding schools, as Islamic educational institutions, face challenges in the development of society and students. This challenge will be easy to face with pesantren education management. This article aims to describe pesantren education management. The method used in this research is the library research method. Data was collected using documentation techniques from scientific journal article literature published online. Data analysis techniques using content analysis techniques, or content analysis, Islamic boarding school education management is management that examines the management and planning of Islamic boarding schools in implementation with the aim of empowering students and the community. Islamic boarding school education management also examines related actions or a system related to the change and development of Islamic boarding schools. Changes and developments occur due to environmental factors.